Inovasi Dan Promosi Unit Usaha Dan Lembaga Pendidikan - Holilur Rahman; Iffatul Aimmah; Madona Agustin Sari (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
The development of the business world and educational institutions is increasingly rapid. Business units and educational institutions are required to be able to compete so that their products can be accepted and survive. Presenting innovation and promotion is a necessity so that business units and educational institutions continue to exist. This research will discuss innovation and promotion of educational institutions. The research method used in this research is qualitative literature study. The results of this study show that innovation in business units can be done by understanding various types of innovation, empowering reliable innovators, redefining metrics and incentives, providing facilities and creating a safe place. Innovation in educational institutions is carried out with 2 models, namely top-down models and bottom-down models. Meanwhile, the promotion of business units and educational institutions is carried out in several stages, namely: planning, organizing, actuating and controlling.